BF gravity. (5th October 2016) - Celada, Mariano; González, Diego; Montesinos, Merced
Abstract: BF gravity comprises all the formulations of gravity that are based on deformations of BF theory. Such deformations consist of either constraints or potential terms added to the topological BF action that turn some of the gauge degrees of freedom into physical ones, particularly giving rise to general relativity. The BF formulations have provided new and deep insights into many classical and quantum aspects of the gravitational field, setting the foundations for the approach to quantum gravity known as spinfoam models. In this review, we present a self-contained and unified treatment of the BF formulations of D -dimensional general relativity and other related models, focusing on the classical aspects of them and including some new results.